ANALYSIS OF TEAMWORK AND HUMAN RESOURCE QUALITY ON EMPLOYEE PERFORMANCE WITH COMMUNICATION AS AN INTERVENING VARIABLE AT THE REGIONAL FINANCE AND ASSET AGENCY NORTH SUMATRA PROVINCE - Elisabeth Kristina Junita Sianipar; Elfitra Desy Surya; Mesra B (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the effect of teamwork and human resource quality on employee performance with communication as an intervening variable at the Regional Finance and Asset Agency of North Sumatra Province. This study uses a quantitative approach with a survey method by distributing 80 questionnaires to employees as respondents. The sample was determined using a purposive sampling technique so that the data obtained was in accordance with the research objectives. The data collected were analyzed using path analysis to determine the direct and indirect effects between variables. The results of the study showed that teamwork had a positive but insignificant effect on employee performance, but communication had a positive and significant effect. Human resource quality had a positive and significant effect on employee performance and through communication. Likewise, communication had a positive and significant effect on employee performance. In addition, teamwork and human resource quality were proven to have a positive and significant indirect effect on employee performance through communication. Thus, communication acts as an intervening variable that mediates the effect of teamwork and human resource quality on employee performance. The results of this study are expected to be input for leaders in improving employee performance through strengthening teamwork, improving human resource quality, and the effectiveness of communication in the work environment.